A Study on Effects of English Songs on Improving Listening Skills of the Third-year English Majors at Phenikaa University - Lê, Lan Chinh (Phenikaa University, 2024)
This graduation paper examines the effects of English songs on improving listening skills among third-year English majors at Phenikaa University. This study employs quantitative and qualitative methods through questionnaires with 100 participants, the research explores students' perceptions and experiences of using English songs to enhance listening skills. The findings reveal that a majority of students believe using songs in listening practice is highly effective. The study concludes that using English songs is an effective tool for improving students' listening skills and offers recommendations for both teachers and students on incorporating this method, suggesting directions for future research.